Who is the beast?: navigating representational and social complexities through the use of animal forms in selected works by Diane Victor - De Harde, Laura (My University, 2014)
Diane Victor has been a prominent figure in the South African artworld since she won the Atelier Award in the 1980s. Since then she has self-inflicted violence into her work; stretched it and stripped it whilst she wrestles with the beast within others and how she portrays that in her work. This research report is concerned with answering the question Who is the ‘Beast’ in the work of Diane Victor? It begins by defining the term ‘Beast’ and situating Victor’s artistic practice in an identified trajectory in Western art history. The report traces the presence of the Beasts in Victor’s work, and follows the metamorphosis of the human form as its internal corruption is explored and revealed through the use of non-human animal parts. Furthermore it investigates the artist’s use of her practice to position herself in relation to the values and conventions inherited from the culture in which she lives. Finally, it provides invaluable insight into who the Beast may have been all along and moreover what it means to be human.
Keywords: Victor, Diane; Women artists; Drawing; South Africa